Principle or standard of evidence?: The understanding of the Peruvian Tax Court about the principle of reliability for the deduction of expenses for the determination of Corporate Income Tax for taxpayers domiciled in Peru during the years 2015 to 2018 - Escudero-Whu, Sandra (2021)
The purpose of this article is to discuss the understanding of the Peruvian Tax Court about the principle of reliability for the deduction of expenses in order to determine the Income Tax for taxpayers domiciled in Peru. To this regard, we are going to explain the legal concepts of principles, rules, and standards of evidence in accordance with the doctrine. In addition, we are going to compare the Peruvian’s legislation and jurisprudence with the Chilean’s and Argentinian’s. Finally, we are going to analyze the jurisprudence issued by Peruvian Tax Court during the years 2015 to 2018.